The Competitive Advantage of Interconnected Firms: An Extension of the Resource-Based View - Lavie, Dovev (Academy of Management Review, 2006)
I extend the resource-based view to incorporate the network resources of interconnected firms. My model distinguishes shared resources from nonshared resources; identifies new types of rent; and illustrates how firm-, relation-, and partner-specific factors determine the contribution of network resources to the rents extracted from alliance networks. After reassessing the heterogeneity, imperfect mobility, imitability, and substitutability conditions, I conclude that the nature of relationships may matter more than the nature of resources in networked environments.